Pollination and dispersal networks in the Amazonian tree flora - Ter Steege, Hans; Ballarin, Caio Simões [UNESP]; Pinto, Carlos Eduardo; Valadão-Mendes, Lorena B.; Stevenson, Pablo; Correa, Diego F.; Giannini, Tereza Cristina; Gomes, Vitor H. F.; McGlone, Matt; de Lima, Renato A. F. (Springer Nature, 2026)
We collected flower-visiting data for 5,201 Amazonian trees species, corresponding to 50% of all known tree species and 94% of all estimated individuals in Amazonia. Bees are the most common flower-visitors responsible for 74% of all studied tree genera and 74.1% of all individual trees, followed by generalist flower-visitors (39.2%). Sixteen tree genera make up 50% of all interactions between tree genera and their flower-visitors. Two of those: Inga, Miconia, each provide more than 2% of all interactions at genus level while six: Protium, Eschweilera, Inga, Pouteria, Ocotea, and Virola each provide more than 2% of all interactions at the estimated tree population level, underscoring the importance of these tree genera in the forest. Forty hyperdominant genera are responsible for half of the fruit resources of the Amazonian disperser community. Nearly 80% of these Amazonian tree species rely on animals for both pollination and seed dispersal, and less than 1% are free from animal involvement in these key life stages. This strong biotic dependence highlights a critical point: animal-mediated interactions are not peripheral but central to the maintenance, regeneration, and spatial structure of Amazonian forests, which makes halting of defaunation in these forests a priority.
Redes de polinização e dispersão na flora arbórea amazônica
Keywords: Amazônia; Polinização por abelhas; Bee pollination